Speaking (Kalam) Learning Strategies Used by Arabic Students at Arabic Courses in Pare: Strategi Balajar Maharah Kalam yang Digunakan oleh Pelajar Bahasa Arab di Lembaga Kursus Pare - Afyuddin, Moh Sholeh; Almustakim, Zezen; Permata, Bagus Andrian; Ma'arif, M. Syamsul (Asalibuna, 2022)
Language learning strategies are understood as characteristics of learners that influence their success in developing language competence. This research focuses on Speaking Skills. The subjects of this study were Fifty Arabic Learners at the Pare Arabic Course Institute. This study aims to (1) Reveal Direct Strategies for learning Arabic at maharoh kalam for learners at the Pare Arabic course institution. (2) Reveal the Indirect Strategy of learning Arabic at maharoh kalam for learners at the Pare Arabic course institution. To answer the purpose of the study, researchers used qualitative descriptive methods. Data collection was carried out through two stages: (1) Using the Oxford Model Questionnaire (1990) as the main data instrument to obtain information about the strategies used by learners in learning Arabic. (2) Teacher informants as additional information about factors influencing the selection of language learning strategies. The results of this study show that: (1) The Dominant Direct Strategy used by learners in the Bitter Melon's Arabic Course Institute is a Cognitive Strategy that has a high percentage, the percentage is: (a) Cognitive Strategy 7.5%, (b) Memory Strategy 4.68%, (c) Compensation Strategy 4.62%. (2) The Dominant Indirect Strategy used by learners in the Pare Arabic Course Institute is the Metacognitive Strategy which has a high percentage, the percentage is: (a) Metacognitive Strategy 9%, (b) Social Strategy 7.81%, (c) Affective Strategy 2.03%. The benefits of this research add insight and information about Arabic learning strategies. Further research can be done that allows for new findings on Arabic learning strategies.